Understanding Technical and Scientific Translation: A Genre-based Approach - Daniel DEJICA (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages, 2020)
In the recent past, 30 or 40 years ago, the terms technical and scientific were used interchangeably when discussing about communication, texts, terms, vocabulary or writing. Due mainly to this reason, the lines separating technical and scientific translation became increasingly blurred and little or no distinction was made between the two terms; as such, technical and scientific translation was regarded as one type of LSP translation. Using genre knowledge, in this article we show that technical translation and scientific translation can and should be treated separately, as two distinct types of LSP translation, for both educational and research purposes. We present two genre-based models for setting-up the technical and scientific curricula, aimed at familiarising students with these inter-related, yet different types of LSP translation, and which can also be used as starting points for research in these two fields.